Scrub Typhus: A Spatial and Temporal Analysis from South India. (29th July 2022) - Kumar, Madhan; Valiaveetil, Koshy Alan; Chandran, Jolly; Mohan, Venkata Raghava; Chandrasekar, K; Ghosh, Urmi; Punnen, Anu; Rose, Winsley
Abstract: Scrub typhus is a zoonotic rickettsial disease caused by the bacterium Orientia tsutsugamushi. The non-specificity of presentation, low index of suspicion and the poor availability of diagnostic tests often lead to delayed diagnosis and significant morbidity and mortality. Temperature, humidity, rainfall and Normalized Difference Vegetation Index (NDVI) on the spatio-temporal clustering of scrub typhus cases in children in three contiguous administrative districts in South India over 5 years were studied. A total of 419 children were diagnosed with scrub typhus during the study period. A surge of children with scrub typhus was noted when the NVDI ranged between 0.6 and 0.8 µm. Temperature, humidity and rainfall had a major role in the incidence of scrub typhus.